A mixture of Aloe Vera Gel (Aloe vera. L) and Sungkai Leaf Extract (Peronema canescens. Jack) as Edible Coating to Increase Tomato (Solanum lycopersicum) Storage Life - Yefrida Yefrida; Fella Krisna Boneta; Refilda Refilda (Andalasian International Journal of Applied Science, Engineering and Technology, 2024)
Tomatoes are climacteric fruits, are well-known for containing lycopene is an antioxidant. The post-harvest shelf life of harvested tomatoes is only 4-5 days. This research aims to optimize previous methods such the use of plastic packaging and cold storage methods were found to be inefficient and produced waste, so it is necessary to renew them by using the edible coating method, a natural ingredient from Aloe vera. L gel, while sungkai leaf extract (Peronema canescans. Jack) shows the effectiveness of edible coating could potentially provide a protective barrier against external factors, helping to maintain the quality of tomatoes and waste reduction. Edible coating material from aloe vera gel added with sungkai leaf extract of various compositions (C, EC1, EC2, EC3, EC4, and EC5) was prapare and applied to tomatoes. Fourier Transform Infrared (FTIR) testing was carried out to determine the functional groups in all edible coating materials. Physicochemical properties tests were carried out on tomatoes. The results obtained by EC5 the lowest weight loss 11.14%, while EC4 was the best edible coating material in percent decay 8.89%, total dissolved solids 1.00oBrix, total antioxidant 0.024 mg AA/g FW, and total phenolic 0.224 mg GAE/g FW for 15 days compared to aloe vera gel coating (EC1), which only lasted for 9 days, and uncoated (C), which only lasted for 6 days. Keywords: Edible coating, physicochemical properties, FTIR